Upskilling and Reskilling in Improving Competence of Competitive Human Resources in the Era of Digital Economy - Anes Arini; Hesti Respatiningsih (Brilliant International Journal Of Management And Tourism, 2024)
This research aims to analyse upskilling and reskilling in improving the competence of competitive human resources in the digital economy era, especially in MSMEs. This research uses descriptive qualitative methods, with data collection through online document searches and literature reviews. The results showed that increasing the competence of MSME HR in the digital economy era is prioritised on how to gather resources and create the right synergy to direct each workforce, especially those with low to high competence. Creating a comprehensive approach to low competency HR can be addressed in a coordinated and coherent manner, comprehensive and ensuring that MSMEs have ongoing support. The implementation of upskiling and reskilling to improve the competence of MSME HR needs to involve the public sector, private sector and other stakeholders so that a good and comprehensive ecosystem is built